PTU-108 Crohn's Disease And Anogenital Granulomatosis Presenting With Genital Oedema. (9th June 2014) - Mellor, R; Gordon, K; Mortimer, P; Pollok, R
Abstract : Introduction: Anogenital granulomatosis (AGG) is a recently recognised cause of genital lymphoedema 1–3 an association of CD with AGG has been noted in previous case reports. 1, 3 It presents with genital erythema and swelling, and flares are frequently misdiagnosed as cellulitis. We present a large case series. Methods: Patients were identified from referrals to the regional to the Lymphoedema Service at St George's Hospital after failure of antibiotics and topical steroids to improve symptoms. Demographic, clinical and endoscopic finding were correlated in patients with histological features of AGG in patients. Results: Sixteen patients (15 male, 1 female; aged 34.8 ± 15.0 yr (mean ± s.d.)), were referred with AGG. 14 of 16 patients initially presented with genital swelling whilst 2 others presented with buttock swelling. Swelling of additional sites was noted in several patients (mons pubis – 25% of patients; natal cleft – 25%; peri-anally – 19%; buttocks – 12.5%). Although initially intermittent (15/16 patients), genital swelling was typically well established and irreversible by the time of presentation to the Lymphoedema Clinic. Flares involved erythema and deterioration of swelling which failed to return to baseline. Established swelling was associated with an increased risk of cellulitis in addition to the non-cellulitic flares. Histological examination of the affected areas demonstrated dermal (and one case of intra-lymphatic) non-caseating granulomas in 12 patients with the remainder diagnosed clinically. Gastroenterology review, including colonoscopy, confirmed a diagnosis of Crohn's disease in 37.5% of patients. Treatment of AGG has proven difficult. Initial treatment with compression garments and prednisolone showed a reduction (but not elimination) of scrotal and penile shaft swelling in 9/11 patients. Antibiotics reduced the frequency of flares in only 3/11 patients. Steroid-sparing immunosuppression was successful in 4/11 patients. In 6 patients, lymphoedema of the foreskin caused difficulties in micturition and therefore circumcision was successfully utilised to improve urinary flow. Debulking surgery has been used in only a small number of our cases to date. Conclusion: AGG should be considered in all patients (especially male) presenting with isolated genital lymphoedema and may unusually be the presenting feature of Crohn's disease. Early diagnosis allows for prompt initiation of systemic immunosuppression therapy which is currently the treatment of choice. We hypothesise that swelling is precipitated by non-infective granulomas blocking lymphatic vessels, research in this regard is in progress. References: Van de Scheur et al . Eur Acad Dermatol Venereol . 2002;17:184–9 Saracino et al . Aus J Dermatol . 2012;Epub Gordon et al . Int J STD AIDS . 2013;Epub Disclosure of Interest: None Declared.